PENGARUH ETOS KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. KIRANA PERMATA - Darman Syafe'i; Titie Syahnaz Natalia; Saifulloh Ibrohim (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
his research haimed to find the influence of work ethic and work motivation onthe performance of employees at PT. Kirana Permata Lubai. The data collectiontechnique used in this research was through the distribution of questionnaires. Thetotal population was 60 employees at PT. Kirana Permata Lubai. The data analysistechnique used was Multiple Linear Regression. Based on the results of theresearch, the work ethic variable had a t-count (5.914) > t-table (2.00247) soHowas rejected and Ha was accepted. This meant that there was an influence ofworkethic on the performance of employees at Kirana Permata Lubai. Mean while,the work motivate on variablet-count (3.546)>t-table (2.00247) so Ho was rejectedand Ha was accepted. This meant that there was an influence of work motivationonthe performance of employees at Kirana Permata Lubai. Simultaneously, the Fcountobtained was 140.114 and F table was 3.16. So F count 140.114>F table 3.16then Ho was rejected and Ha was accepted, meaning simultaneously there was asignificant influence of work ethic and work motivation on the performance ofemployees at Kirana Permata Lubai.The coefficien t of determination (R2) obtainedwas 0.831.This meant that the contribution of th einfluence of work ethic and workmotivation on the performance of employees was 83.1%, while the remaining16.9% was influenced by other variables not included in this research modelsuchasability and expertise (Simamora cited in Budiasa, 2021,15).